Detection of the I1781L mutation in fenoxaprop‐p‐ethyl‐resistant American sloughgrass (Beckmannia syzigachne Steud.), based on the loop‐mediated isothermal amplification method. Issue 1 (15th April 2014) - Pan, Lang; Li, Jun; Zhang, Wen‐na; Dong, Liyao
Abstract BACKGROUND The increasing use of fenoxaprop‐p‐ethyl has resulted in evolved resistance in American sloughgrass (Beckmannia syzigachne Steud.). Target‐site‐based resistance to acetyl‐CoA carboxylase (ACCase) inhibitors in B. syzigachne occurs owing to an isoleucine‐to‐leucine substitution at residue 1781 (I1781L) of the ACCase enzyme. A rapid detection method is needed to identify the resistance‐conferring substitution. RESULTS Four populations of B. syzigachne that were resistant to fenoxaprop‐p‐ethyl and contained the I1781L substitution were identified. Conventional PCR and derived cleaved amplified polymorphic sequence (dCAPS) methods were used to detect the mutation. Additionally, a rapid nucleic acid detection method, loop‐mediated isothermal amplification (LAMP), was successfully developed and used to detect the genetic mutation underlying the I1781L substitution in the B. syzigachne ACCase enzyme. CONCLUSION This report is the first to describe the application of a LAMP assay for mutation detection in herbicide‐resistant weeds. The assay does not require specialised equipment: only a standard laboratory bath is needed. This technique could be employed for detecting the I1781L substitution in B. syzigachne plants and seeds. © 2014 Society of Chemical Industry